2019
DOI: 10.3389/fmicb.2019.02767
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Klebsiella pneumoniae KPC Clones Contribute to an Extended Hospital Outbreak

Abstract: The circulation of carbapenem-resistant Klebsiella pneumoniae (CRKP) is a significant problem worldwide. In this work we characterize the isolates and reconstruct the spread of a multi-clone epidemic event that occurred in an Intensive Care Unit in a hospital in Northern Italy. The event took place from August 2015 to May 2016 and involved 23 patients. Twelve of these patients were colonized by CRKP at the gastrointestinal level, while the other 11 were infected in various body districts. We retrospectively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…To show the capability of MeltingPlot, we simulated a complex large Klebsiella pneumoniae nosocomial outbreak (100 outbreak isolates) sustained by multiple clones spread in different wards, a situation comparable to real large nosocomial outbreaks [ 13 ]. The isolates were simulated using HRM temperatures retrieved from a dataset of K. pneumoniae isolates previously analyzed in our laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…To show the capability of MeltingPlot, we simulated a complex large Klebsiella pneumoniae nosocomial outbreak (100 outbreak isolates) sustained by multiple clones spread in different wards, a situation comparable to real large nosocomial outbreaks [ 13 ]. The isolates were simulated using HRM temperatures retrieved from a dataset of K. pneumoniae isolates previously analyzed in our laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…Doing so revealed that each of the top three K loci were dominated by a single ST (83.5% of KL107 were ST512; 93.0% of KL105 were ST11; 91.4% of KL17 were ST101). Importantly, the vast majority of ST512-KL107 genomes (75.3%) originated from Italy where this ST is known to be locally circulating 46,47 , while 58% of ST11-KL105 originated from Poland and Slovakia, and 56% of ST101-KL17 originated from Serbia and Romania. When these putative local expansions were excluded, the top 6 K loci were (KL24, KL15, KL2, KL112, KL107, KL151) and accounted for just 34% of the remaining genomes.…”
Section: Resultsmentioning
confidence: 99%
“…To show the capability of MeltingPlot, we simulated a large K. pneumoniae outbreak (100 isolates) sustained by multiple clones, a situation observed in real nosocomial outbreaks [11]. We used HRM temperatures extracted from a dataset of K. pneumoniae isolates previously analyzed in our laboratory.…”
Section: Introductionmentioning
confidence: 99%